Method for producing boron nitride

By calcining melamine borate with a flux to control particle shape and size, the method addresses boron nitride's anisotropy issue, improving thermal conductivity and expanding its application in insulating films and device interlayers.

JP7627484B2Active Publication Date: 2025-02-06SHINSHU UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021007381
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-20
Publication Date
2025-02-06
Estimated Expiration
2041-01-20

AI Technical Summary

Technical Problem

Boron nitride's large anisotropy of thermal conductivity due to its crystal structure and scale shape reduces thermal conductivity when used as a resin filler, and controlling particle size is necessary for improved filling properties.

Method used

A method involving the production of boron nitride by calcining melamine borate in the presence of a flux, with controlled conditions such as temperature, molar ratio, and use of lithium carbonate or lithium hydroxide as the flux agent, to maintain the shape and size of melamine borate particles.

Benefits of technology

The method produces boron nitride particles with reduced anisotropy, maintaining desired size and shape, enhancing thermal conductivity and enabling applications in thin insulating films and interlayer insulating films for devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627484000001
    Figure 0007627484000001
  • Figure 0007627484000002
    Figure 0007627484000002
  • Figure 0007627484000003
    Figure 0007627484000003
Patent Text Reader

Abstract

To provide a method for producing boron nitride capable of controlling the shape and size of boron nitride particles.SOLUTION: A method for producing boron nitride comprises a step of obtaining melamine borate by slowly cooling or ultrasonic treatment of a saturated aqueous solution of boric acid and melamine, and a firing step of firing the melamine borate in the presence of a lithium compound as a flux at a temperature of 1000 to 1700°C to obtain boron nitride. The method can give large-diameter columnar particles of boron nitride, which therefore has a filling property to a resin that is better than that of conventional scaly particles and has excellent thermal conductivity.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing boron nitride. [Background technology]

[0002] Boron nitride has high thermal conductivity and is chemically and thermally stable, which is why it is increasingly being used as a thermally conductive filler. Boron nitride can be produced by reacting a compound containing boron with a compound containing nitrogen. For example, Patent Document 1 describes a method for producing hexagonal boron nitride primary particle aggregates by two-stage calcination of melamine borate under specific conditions. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-104253 A Summary of the Invention [Problem to be solved by the invention]

[0004] Boron nitride is known to have a large anisotropy in thermal conductivity due to its crystal structure and scale shape. Therefore, when it is used as a thermally conductive filler in resin, there is a problem that the thermal conductivity is easily reduced due to the orientation of boron nitride in the resin. Furthermore, when filling a resin with boron nitride as a filler, it is necessary to control the particle size of the melamine borate in order to further improve the filling property.

[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a method for producing boron nitride that can control the shape and size of boron nitride particles. [Means for solving the problem]

[0006] The present invention encompasses the following [1] to [4]. [1] A method for producing boron nitride, comprising: a step of obtaining melamine borate; and a step of calcining the melamine borate in the presence of a flux at a temperature of 1000°C or higher and 1700°C or lower to obtain boron nitride. [2] The method for producing boron nitride according to [1], wherein the step of obtaining melamine borate comprises a step of ultrasonically treating a saturated aqueous solution of boric acid and melamine. [3] The method for producing boron nitride according to [1] or [2], wherein in the firing step, the melamine borate and the flux are mixed and fired in a molar ratio (melamine borate / flux) of 1 or more and 4 or less. [4] The method for producing boron nitride according to any one of [1] to [3], wherein the flux is lithium carbonate or lithium hydroxide. Effect of the Invention

[0007] According to the present invention, it is possible to provide a method for producing boron nitride that allows control of the shape and size of boron nitride particles. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 shows the X-ray diffraction pattern of melamine borate. [Diagram 2] 1 is a scanning electron microscope photograph of melamine borate. [Diagram 3] FIG. 1 is a diagram showing an X-ray diffraction pattern of the boron nitride produced in Example 1. [Figure 4] 1 is a scanning electron microscope photograph of the boron nitride produced in Example 1. [Diagram 5] 1 is a scanning electron microscope photograph of the melamine borate produced in Example 2. [Figure 6] 1 is a scanning electron microscope photograph of the boron nitride produced in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <How to manufacture boron nitride> The method for producing boron nitride of the present embodiment includes a step of obtaining melamine borate and a firing step of firing the melamine borate in the presence of a flux. The inventors have found through their research that calcining melamine borate in the presence of a flux makes it possible to produce boron nitride that maintains the particle size and shape of the melamine borate.The present invention relates to the technical idea of ​​controlling the particle shape and size of the produced boron nitride within a desired range by controlling the particle shape and size of the melamine borate in the process of obtaining the melamine borate.

[0010] [Step for obtaining melamine borate] Melamine borate can be obtained, for example, by recrystallizing melamine borate from a saturated aqueous solution containing boric acid and melamine. Hereinafter, the term "saturated aqueous solution" refers to a saturated aqueous solution containing boric acid and melamine.

[0011] In the subsequent calcination step, when the melamine borate is calcined in the presence of a flux, the size and shape of the melamine borate particles are maintained, and therefore the size and shape of the melamine borate are controlled to obtain boron nitride of the desired size and shape.

[0012] For example, when it is desired to produce boron nitride having a particle size of about 5 μm to 10 μm, it is preferable to produce melamine borate having a particle size of about 5 μm to 10 μm. The above particle size range can be appropriately changed depending on the desired size of boron nitride.

[0013] When producing boron nitride secondary particles having an elongated columnar shape and an aspect ratio, which is the ratio of the minor axis diameter to the major axis diameter, of about 1 to 1.5, it is preferable to produce melamine borate having an aspect ratio, which is the ratio of the minor axis diameter to the major axis diameter, of about 1 to 1.5. The above aspect ratio range can be appropriately changed depending on the desired size of the boron nitride.

[0014] The size and shape of the melamine borate particles can be controlled by controlling the recrystallization conditions and post-treatment. The recrystallization conditions are heating and cooling conditions of a saturated aqueous solution or ultrasonic treatment conditions of a saturated aqueous solution. The post-treatment can be a dry grinding method or mechanical grinding using a ball mill or the like.

[0015] In one embodiment of the present invention, the step of obtaining melamine borate is a step of heating and cooling a saturated aqueous solution. In one embodiment of the present invention, the step of obtaining melamine borate is a step of subjecting a saturated aqueous solution to ultrasonic treatment, followed by suction filtration.

[0016] (Heating and cooling process) First, a predetermined amount of boric acid is completely dissolved in pure water heated to about 95°C. Next, a predetermined amount of melamine is added and stirred until the melamine is completely dissolved. This operation produces a saturated aqueous solution.

[0017] The amount of boric acid is, for example, 1 g or more and 5 g or less, and preferably 2 g or more and 4 g or less, per 100 mL of distilled water. The amount of melamine is, for example, 0.5 g to 4 g, and preferably 1 g to 3 g, per 100 mL of distilled water.

[0018] The saturated aqueous solution is allowed to cool, whereby crystals of melamine borate are precipitated. As an example of the cooling conditions, it is preferable to immerse the beaker containing the obtained saturated aqueous solution in a 1 L beaker containing hot water at 50°C or more and 100°C or less, and leave it at room temperature for about 12 hours or more and 24 hours or less to slowly cool the saturated aqueous solution.

[0019] The precipitate is dried to obtain melamine borate. The method for drying the precipitate may be natural drying or drying at room temperature or in a thermostatic chamber at 100° C. or lower.

[0020] The heating and cooling process produces melamine borate particles having a columnar, elongated shape. The minor axis of the melamine borate particles is about 5 μm to 10 μm, and the major axis is about 10 μm to 2 cm.

[0021] (Ultrasonic treatment and suction filtration process) In this embodiment, it is preferable to ultrasonically treat the saturated aqueous solution obtained by the same method as above. In this case, for example, an ultrasonic cleaner may be used to perform the ultrasonic treatment. Crystals of melamine borate are precipitated by the ultrasonic treatment. For example, an ultrasonic cleaner can be used for the ultrasonic treatment.

[0022] By changing the conditions of ultrasonic treatment, the shape and size of the produced melamine borate particles can be controlled. By ultrasonic treatment, columnar particles are crushed, and melamine borate particles with minor and major axis diameters of several tens of μm are obtained.

[0023] The conditions for ultrasonic treatment include frequency and treatment time. The frequency is preferably adjusted to a range of 20 kHz to 50 kHz. The treatment time is preferably adjusted to a range of 1 minute to 10 minutes.

[0024] The combination of frequency and processing time is, for example, 20 kHz or more and 50 kHz or less, and 1 minute or more and 10 minutes or less.

[0025] The longer the treatment time, the smaller the size of the resulting melamine borate and the higher the aspect ratio. Also, the higher the frequency, the smaller the size of the resulting melamine borate.

[0026] For example, when 1 g of melamine borate is added to 100 mL of saturated solution, ultrasonic treatment for 5 minutes with a power consumption of 430 W, a high-frequency output of 300 W, and an oscillation frequency of 38 kHz will produce melamine borate particles with a particle size of several tens of μm.

[0027] After the ultrasonic treatment, the resulting crystals are preferably filtered under suction to obtain melamine borate particles.

[0028] The shape and size of the produced melamine borate particles can be confirmed by observation with a scanning electron microscope.

[0029] By carrying out ultrasonic treatment, it becomes easier to obtain melamine borate particles having an aspect ratio, which is the ratio of the minor axis diameter to the major axis diameter, of about 1 to 1.5.

[0030] [Firing process] The calcination step is a step in which the melamine borate is calcined in the presence of a flux. Calcination of melamine borate in the presence of a flux can produce boron nitride which retains the particle shape and size of the melamine borate.

[0031] The firing temperature is from 1000°C to 1700°C, preferably from 1100°C to 1600°C, and more preferably from 1200°C to 1500°C. When the firing temperature is within the above range, boron nitride that maintains the size and shape of the melamine borate is easily obtained. When the firing temperature is equal to or higher than the lower limit, the crystal growth of boron nitride is likely to proceed. If the firing temperature exceeds the upper limit, the boron nitride will crystallize and tend to grow in a scaly form, so in order to obtain particulate boron nitride, it is preferable to fire at a temperature of 1700° C. or lower.

[0032] In this embodiment, the "firing temperature" refers to the maximum temperature that the atmosphere in the firing furnace is maintained at in the firing step.

[0033] The time for which the firing temperature is maintained is preferably from 30 minutes to 2 hours, and more preferably from 50 minutes to 90 minutes.

[0034] In this embodiment, the firing step is preferably carried out in an atmosphere of an inert gas, such as nitrogen gas or argon gas.

[0035] In the firing step, the rate of temperature rise until the firing temperature is reached is, for example, 200° C. / hour or more and 400° C. / hour or less, and preferably 250° C. / hour or more and 350° C. / hour or less.

[0036] In this embodiment, the "heating rate" is calculated from the time from when the heating starts in the firing device to when the maximum holding temperature is reached, and the temperature difference from the temperature at the start of heating in the firing furnace of the heating device to the pore holding temperature.

[0037] After firing, the resulting fired product may be washed with water.

[0038] In the firing step, the melamine borate is fired in the presence of a flux. The flux is not particularly limited as long as it is a commonly used flux, and specific examples thereof include lithium borate, sodium borate, potassium borate, boron oxide, sodium nitrate, sodium chloride, potassium chloride, lithium chloride, sodium carbonate, potassium carbonate, lithium carbonate, sodium sulfate, potassium sulfate, lithium sulfate, sodium acetate, potassium acetate, lithium acetate, sodium oxalate, potassium oxalate, lithium oxalate, sodium citrate, potassium citrate, lithium citrate, sodium oxide, potassium oxide, lithium oxide, sodium hydroxide, potassium hydroxide, lithium hydroxide, sodium fluoride, potassium fluoride, lithium fluoride, and mixtures thereof, as well as ammonium salts corresponding thereto.

[0039] In this embodiment, the flux preferably uses lithium carbonate or lithium hydroxide.

[0040] In the firing step, it is preferable to mix and fire the melamine borate and the flux in a molar ratio (melamine borate / flux) of 1 or more and 3 or less.

[0041] By firing in the presence of a flux, boron nitride crystals can be grown at low temperatures below 1700°C. This makes it difficult for boron nitride to grow in a scaly form, and makes it possible to produce boron nitride that maintains the shape and size of the melamine borate particles.

[0042] <Boron nitride> The boron nitride produced by the production method of this embodiment maintains the particle shape and size of the raw material melamine borate. The boron nitride of this embodiment is a secondary particle that is an aggregate of primary particles. The secondary particle is porous and has minute pores with a pore diameter of about 10 nm.

[0043] The boron nitride of this embodiment is, for example, a secondary particle having an elongated columnar shape, with a minor axis diameter of about 5 μm to 10 μm and a major axis diameter of about 10 μm to 2 cm. The boron nitride of this embodiment is, for example, a secondary particle whose minor axis and major axis are each several tens of μm, and whose aspect ratio is about 1 to 1.5.

[0044] The boron nitride of this embodiment has smaller anisotropy of thermal conductivity than conventional flake boron nitride, so it is expected that the thermal conductivity of the thermal conductor as a whole will be improved. In addition, because the size and shape of the boron nitride particles can be controlled, it can be used in a wide range of applications, such as thin insulating films with excellent thermal conductivity and interlayer insulating films for devices. EXAMPLES

[0045] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0046] <Example 1> [Step for obtaining melamine borate] 3 g of boric acid was added to 100 mL of distilled water heated to 80°C, and the mixture was stirred until completely dissolved. Next, 2 g of melamine was added and stirred until completely dissolved. A stirrer was used for stirring. This resulted in a saturated aqueous solution of boric acid and melamine.

[0047] The beaker containing the obtained saturated aqueous solution was immersed in a 1 L beaker containing hot water at 80°C and left at room temperature for about 12 hours, and the saturated aqueous solution was slowly cooled. Upon cooling, crystals of melamine borate were precipitated. The precipitated crystals of melamine borate were taken out into a petri dish and left at room temperature for 12 hours to dry naturally, thereby obtaining precipitate 1.

[0048] An X-ray diffraction pattern was obtained for the precipitate 1. The result is shown in Figure 1(a).

[0049] As shown in Figure 1(b), by referring to the Powder X-ray Diffraction Database (ICDD), it was confirmed that the compound was C4H3NO2, ICDD No. 050-2384.

[0050] Furthermore, as shown in Figure 1(c), it was confirmed that the precipitate was melamine borate (ICDD No. 076-6949). From the results in Figure 1(c), it was confirmed that the precipitate 1 was melamine borate 1.

[0051] An SEM photograph (magnification: 3000 times) of the obtained melamine borate 1 is shown in Fig. 2. As shown in Fig. 2, the melamine borate 1 had a long and thin columnar shape, and the minor axis diameter was about 5 µm to 10 µm.

[0052] [Firing process] 2 mmol of melamine borate 1 and 1 mmol of lithium carbonate were mixed for 10 minutes to obtain mixture 1. Mixture 1 was placed in a square carbon crucible and fired using a Keramax box electric furnace. The molar ratio of the flux to the melamine borate (melamine borate / flux) was 2.

[0053] First, the temperature was raised to 1400°C over 4 hours and 20 minutes at a heating rate of 300°C / hour, and then held at 1400°C for 1 hour. Then, the temperature was lowered to 0°C over 4 hours and 20 minutes at a cooling rate of 300°C / hour. Nitrogen gas was circulated at a flow rate of 0.2 L / min during all of the heating, holding at 1400°C, and cooling steps. This resulted in the production of fired product 1. Fired product 1 was washed with water to obtain fired product 1.

[0054] An X-ray diffraction pattern was obtained for the obtained fired product 1. Figure 3(a) shows the X-ray diffraction pattern of fired product 1 before washing with water. Figure 3(b) shows the X-ray diffraction pattern of fired product 1 after washing with water. No peaks attributed to lithium carbonate were confirmed in either Figure 3(a) or (b).

[0055] As shown in Figure 3(c), when referring to ICDD, it was confirmed that it was boron nitride, ICDD No. 034-0421. From the results in Figure 3(c), it was confirmed that sintered product 1 was boron nitride 1.

[0056] Figure 4(a) shows an SEM photograph (magnification 2000x) of boron nitride 1, and Figure 4(b) shows an SEM photograph (magnification 20000x). Figure 4(a) shows that boron nitride 1 has a columnar, elongated shape with a minor axis diameter of approximately 5μm to 10μm. In other words, it was confirmed that the shape and size of melamine borate 1 were maintained.

[0057] From FIG. 4(b), it was confirmed that melamine borate 1 has a porous structure with multiple pores with a pore diameter of about 10 nm.

[0058] <Example 2> [Step for obtaining melamine borate] 3 g of boric acid was added to 100 mL of distilled water heated to 80°C, and the mixture was stirred until completely dissolved. Next, 2 g of melamine was added and stirred until completely dissolved. A stirrer was used for stirring. This resulted in a saturated aqueous solution of boric acid and melamine.

[0059] The resulting saturated aqueous solution was subjected to ultrasonic treatment for 5 minutes to precipitate crystals of melamine borate. The resulting crystals were filtered under suction to obtain Precipitate 2.

[0060] An X-ray diffraction pattern was obtained for the precipitate 2. The result confirmed that the precipitate 2 was melamine borate.

[0061] FIG. 5(a) shows an SEM photograph (500x) of the obtained melamine borate 2. FIG. 5(b) shows an SEM photograph (1000x) of the obtained melamine borate 2. As shown in FIG. 5(a), the melamine borate 2 had a particulate shape, and the minor axis diameter and major axis diameter of the particles were each about 20 μm. The aspect ratio (minor axis diameter / major axis diameter) of the melamine borate 2 was about 1.

[0062] [Firing process] 4 mmol of melamine borate 2 and 2 mmol of lithium carbonate were mixed for 10 minutes to obtain mixture 2. Mixture 2 was placed in a square carbon crucible and fired using a Keramax box electric furnace. The molar ratio of the flux to the melamine borate (melamine borate / flux) was 2.

[0063] First, the temperature was raised to 1400°C over 4 hours and 40 minutes at a heating rate of 300°C / hour, and then held at 1400°C for 1 hour. Then, the temperature was lowered to 0°C over 4 hours and 20 minutes at a cooling rate of 300°C / hour. Nitrogen gas was circulated at a flow rate of 0.2 L / min during all of the heating, holding at 1400°C, and cooling steps. This resulted in the production of the fired product 2. The fired product 2 was washed with water to obtain the fired product 2.

[0064] An X-ray diffraction pattern was obtained for the obtained fired product 2. From this, it was confirmed that fired product 2 was boron nitride 2.

[0065] FIG. 6(a) shows an SEM photograph (magnification: 1000 times) of boron nitride 2, and FIG. 6(b) shows an SEM photograph (magnification: 2000 times). From Fig. 6(a), it was confirmed that the boron nitride 2 had a particle shape, with the minor axis diameter and major axis diameter of the particle each being approximately 20 µm. In addition, the aspect ratio (minor axis diameter / major axis diameter) of the boron nitride 2 was approximately 1. In other words, it was confirmed that the shape and size of the melamine borate 2 were maintained.

[0066] Figure 6(c) shows a 40,000x SEM image of boron nitride 2. Figure 6(c) confirms that melamine borate 2 has a porous structure with multiple pores with a diameter of about 10 nm.

Claims

1. Obtaining melamine borate; A calcination step of calcining the melamine borate in the presence of a flux at a temperature of 1000° C. or more and 1700° C. or less to obtain boron nitride, In the firing step, the melamine borate and the flux are mixed and fired in a molar ratio (melamine borate / flux) of 1 to 3, The method for producing boron nitride, wherein the flux is lithium carbonate or lithium hydroxide.

2. 2. The method of claim 1, wherein the step of obtaining melamine borate comprises ultrasonically treating a saturated aqueous solution of boric acid and melamine.

Citation Information

Patent Citations

  • Amorphous boron nitride powder

    JP1999302004A

  • Method for producing hexagonal boron nitride

    JP2010100448A

  • Composite particle of melamine borate and boron nitride, and method for producing boron nitride particle using the same

    JP2012171842A

  • Hexagonal boron nitride single crystal, method for manufacturing the same, composite material composition mixed with hexagonal boron nitride single crystal and heat dissipation member obtained by molding composite material composition

    JP2016141600A

  • Hexagonal boron nitride primary particle aggregate and application of the same

    JP2018104253A